OPTIMIZING PRODUCTIVE WAQF THROUGH SMALL AND MEDIUM ENTERPRISES (SMEs) FINANCING BASED ON GREEN ECONOMY - Siregar, Lukman Hakim; Nurhayati, Nurhayati; Nasution, Yenni Samri Juliati (Universitas Dharmawangsa Medan, 2024)
There is an effort to examine economic activities in an Islamic manner in response to current economic issues. Various discussions, training, workshops, and seminars have been conducted concerning the revitalization of waqf institutions, which are an essential part of Islamic economic instruments. The formation of green entrepreneurship is necessary to support sustainable economic independence. This can be established by optimizing waqf funds by providing financing to Small and Medium Enterprises (SMEs). Waqf plays a role in addressing social problems in society. Poverty, unemployment, malnutrition, and school dropouts can be addressed through the empowerment and management of waqf as a source of funding for the ummah. This research uses library research with a descriptive qualitative method, noting findings regarding global concepts in each discussion within the research derived from literature and recent sources. In this context, it concerns productive waqf. After recording, it then integrates the findings, whether theory or research results from the reading sources. Financing through the waqf instrument is one form of productive waqf management. This scheme is implemented by providing and distributing the benefits of waqf through financing schemes given to the mauquf alaih or the recipients of waqf benefits.